2021
DOI: 10.18662/po/12.3/340
|View full text |Cite
|
Sign up to set email alerts
|

Big-Five Personality Traits and Cognitive Skills in Higher Education in the Pandemic Context

Abstract: The SARS-Cov-2 pandemic created a severe psychosocial and medical shock all over the world. For more than a year, humanity struggled with adjusting to different measures that governments imposed on the population worldwide. Educational systems all over the world were forced to comply with the new conditions of activity. In this context, different reactions emerged, and skills were used and developed. The coronavirus pandemic was and still is a stressful worldwide event that disrupted, among numerous other thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These issues and challenges are related to infrastructure, teaching and learning activities, socio-psychological aspects, emotional aspects of learning, and institutional policies. The unavailability of the infrastructure required for the continuation of uninterrupted teaching and learning activities is a major challenge, particularly in the least developed countries such as Nepal, Bangladesh and Pakistan (Bhagat and Kim, 2020; Devkota, 2021; Salceanu, 2020). Many students in these countries lack devices, reliable internet services and uninterrupted electricity supplies that are essential for online classes (Acharya et al, 2021; Asgher and Hanif, 2021; Gautam and Gautam, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These issues and challenges are related to infrastructure, teaching and learning activities, socio-psychological aspects, emotional aspects of learning, and institutional policies. The unavailability of the infrastructure required for the continuation of uninterrupted teaching and learning activities is a major challenge, particularly in the least developed countries such as Nepal, Bangladesh and Pakistan (Bhagat and Kim, 2020; Devkota, 2021; Salceanu, 2020). Many students in these countries lack devices, reliable internet services and uninterrupted electricity supplies that are essential for online classes (Acharya et al, 2021; Asgher and Hanif, 2021; Gautam and Gautam, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results underline that the success of distance learning in many ways depends on the extent to which it accommodates the psychological traits of students, who are forced to acquire new knowledge without traditional instructional methods. Sălceanu [13] tried to assess Big 5 personality concepts and she found that conscientious people, who respect norms and rules, who are organized and plan their actions, and who strive to do things right and are trustworthy are also able to identify logical regularities and to apply those rules in problematic situations. They also show the easiness of combining information from different premises in order to achieve a valid conclusion.…”
Section: The Role Of Personality In Distance Learning Adoption and Pe...mentioning
confidence: 99%